Comparative Abilities of Body Mass Index, Waist Circumference, Abdominal Volume Index, Body Adiposity Index, and Conicity Index as Predictive Screening Tools for Metabolic Syndrome among Apparently Healthy Ghanaian Adults - Lawrence Quaye; William Kwame Boakye Ansah Owiredu; Nafiu Amidu; Peter Paul Mwinsanga Dapare; Yussif Adams (Journal of Obesity)
The prevalence of the metabolic syndrome (MetS) continues to increase. There is therefore the need for early detection to avert possible adverse outcomes. Several anthropometric methods have been suggested to predict MetS, but no consensus has been reached on which is best. The aim of the study was to explore the comparative abilities of conicity index, body adiposity index, abdominal volume index, body mass index, and waist circumference in predicting cardiometabolic risk among apparently healthy adults in the Tamale metropolis. This study was a cross sectional study conducted from September 2017 to January 2018, among one hundred sixty (160) apparently healthy normoglycemic normotensive adults. A self-designed questionnaire was administered to gather sociodemographic data. Anthropometric and haemodynamic measurements were also taken. Blood samples were collected for fasting blood glucose (FBG) and lipid profile. MetS was classified using the harmonised criteria as indicated by the joint interim statement (JIS). Of 160 participants, 42.5% were male and 57.5% were female. Body mass index (BMI) and waist circumference (WC) associated better with MetS and other cardiovascular risk factors. Generally, BMI and WC showed largest area under curves (AUCs) than abdominal volume index (AVI), body adiposity index (BAI), and conicity index (CI) in predicting MetS and its components. Upon gender stratification, AVI and CI had the larger AUCs in females whiles BMI remained the superior index in males. Whiles BMI and WC remained useful parameters, they were not useful in predicting MetS and its components in the female population in this study.